(3GdYdGbI Hjf GdeTJQj hGdehQO (B:s (3eONd ddJShjb HGdYdGbGJ (B/s - (3QLH, LjgGf YHO GdefYes ((3GdbGgQI(B: s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2006)
(3jVe eGgjI GdJShjb HGdYdGbGJ, GdfeGPL hGdfXQjGJ GdJj JOYe GdJShjb HGdYdGbGJ, GdOQGSGJ GdMOjKI GdeJYdbI HGdfehPL GdebJQM dYdGbGJ GdeTJQj, QDjI fXQjI ddfehPL GdebJQM dYdGbGJ GdeTJQj(B((3GdehQO(B)s
(3HHdjhZQGajG(B: (3U(B.301s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdYdGbGJ GdYGeIs